The Business of Benevolence : Industrial Paternalism in Progressive America - Tone, Andrea, 1964- (Book collections on Project MUSE., 1997)
In the early twentieth century, an era characterized by unprecedented industrial strife and violence, thousands of employers across the United States pioneered a new policy of labor relations called welfare work. The paternalistic practices and forms of compensation they introduced were designed not only to control workers but also to advertise the humanity of corporate capitalism and thus to thwart the advance of legislated reform. In a penetrating contribution to a burgeoning literature on the development of the U.S. welfare state, Andrea Tone offers a new interpretation of the role of welfare capitalism in the shaping of that development.